2023
DOI: 10.1002/ece3.10063
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the potential of social media and citizen science data to track changes in species' distributions

Abstract: How to best track species as they rapidly alter their distributions in response to climate change has become a key scientific priority. Information on species distributions is derived from biological records, which tend to be primarily sourced from traditional recording schemes, but increasingly also by citizen science initiatives and social media platforms, with biological recording having become more accessible to the general public. To date, however, our understanding of the respective potential of social m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…It is undeniable that citizen science has brought benefits for data collection and by bringing people closer to nature (Forti & Szabo, 2023; O'Neill et al, 2023). However, at least in Brazil, citizen science platforms such as iNaturalist have also been used to share images of species recorded during environmental impact assessments, often without voucher specimens deposited in natural history collections, as the register of A. anomala presented here.…”
Section: Figurementioning
confidence: 99%
“…It is undeniable that citizen science has brought benefits for data collection and by bringing people closer to nature (Forti & Szabo, 2023; O'Neill et al, 2023). However, at least in Brazil, citizen science platforms such as iNaturalist have also been used to share images of species recorded during environmental impact assessments, often without voucher specimens deposited in natural history collections, as the register of A. anomala presented here.…”
Section: Figurementioning
confidence: 99%
“…Recent assessments of iNaturalist data have shown that accurate species identification as well as completeness of contribution was possible to a high degree for some (usually more charismatic) species (Mesaglio et al 2023) and that it improves with screening and training of volunteers (Wittmann, Girman, and Crocker 2019). Data from iNaturalist can be useful to track changes in species distributions, especially when used in combination with museum records and scientific surveys (Gaier and Resasco 2023;O'Neill et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Citizen science is playing a vital role in reducing global biodiversity knowledge gaps (Callaghan et al, 2021(Callaghan et al, , 2022Chandler et al, 2017;Di Minin et al, 2015;Pocock et al, 2019), and, even in Europe, around 80−90% of biodiversity observational records are collected by dedicated volunteers (Schmeller et al, 2009). Amateur (and professional) naturalists are increasingly taking advantage of expanded internet coverage and the photographic capacity of mobile devices to share their observations online (Andrachuk et al, 2019;Chowdhury, Aich, et al, 2023;Marcenò et al, 2021;O'Neill et al, 2023). Consequently, the amount of biodiversity data from citizen science in the Global Biodiversity Information Facility (GBIF) is sharply increasing, although its data are biased toward Europe and North America (Hughes et al, 2021).…”
Section: Introductionmentioning
confidence: 99%